Approximating the global economic (market) value of farmed animals - Schrobback, P.; Dennis, G.; Li, Y.; Mayberry, D.; Shaw, A.; Knight-Jones, Theodore J.D.; Marsh, T.L.; Pendell, Dustin L.; Torgerson, Paul R.; Gilbert, W.; Huntington, B.; Raymond, K.; et al. (Elsevier, 2023)
Understanding the global economic importance of farmed animals to society is essential as a baseline for decision making about future food systems. We estimated the annual global economic (market) value of live animals and primary production outputs, e.g., meat, eggs, milk, from terrestrial and aquatic farmed animal systems. The results suggest that the total global market value of farmed animals ranges between 1.61 and 3.3 trillion USD (2018) and is expected to be similar in absolute terms to the market value of crop outputs (2.57 trillion USD). The cattle sector dominates the market value of farmed animals. The study highlights the need to consider other values of farmed animals to society, e.g., finance/insurance value and cultural value, in decisions about the sector’s future.